Liturgical assumptions Dionysius’ Christology - Петровић, Предраг (Sabornost - The Theological Year-book, 2013)
Dionysius speaks of “substantial secrets” of the Lord’s benevolence, while Saint Maximus the Confessor, in his Scholia on substantial secrets, interprets as events related to the Lord’s Incarnation such as hunger, hard work, walking on the water, entering through the shouted door, the resurrection of the dead, and the like. Separated from the broader context of St Maksimus’ theology, the Dionisije’s attitude could be understood only through the historically divided actions of the Lord’s God-made-man personality. The author, therefore, analyzes the question whether the words of Dionysius substantial secret relate to our liturgically-symbolic existence, or does this explicitly come to the mysteries of the God-made-man personality that took place individually two thousand years ago? He concludes that the Maksimus’ theological explanations, given elsewhere in his Sholia, entitle the right that reality, hidden behind the Dionisius’ term “substantial secrets”, we identify it with mistagogically Christological ways of the hierarchical existance of the Church.